2013
DOI: 10.1039/c3mb25582d
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein profiling of renal cell carcinoma urinary exosomes

Abstract: aRenal cell carcinoma (RCC) accounts for about 3% of all human malignancies and its incidence is increasing. There are no standard biomarkers currently used in the clinical management of patients with renal cell carcinoma. A promising strategy for new biomarker detection is comparative proteomics of urinary exosomes (UE), nanovesicles released by every epithelial cell facing the urinary space, enriched in renal proteins and excluding high-abundance plasmatic proteins, such as albumin. Aim of the work is to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 54 publications
(85 reference statements)
1
102
0
Order By: Relevance
“…Comparison of the protein pattern of urinary exosomes of a healthy subject (UE) with the urine (U) of origin, after sediment removal. UE were isolated by the ultracentrifugation protocol, and urine proteins were concentrated by ultrafi ltration [ 11 ]. Their protein profi les are very different, as expected: albumin, responsible for the main band appearance in urine, results depleted in UE, while THP is predominant.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Comparison of the protein pattern of urinary exosomes of a healthy subject (UE) with the urine (U) of origin, after sediment removal. UE were isolated by the ultracentrifugation protocol, and urine proteins were concentrated by ultrafi ltration [ 11 ]. Their protein profi les are very different, as expected: albumin, responsible for the main band appearance in urine, results depleted in UE, while THP is predominant.…”
Section: Methodsmentioning
confidence: 77%
“…Many different protocols are available to prepare urinary proteins. We used ultrafi ltration by concentrator devices, as described by Raimondo et al [ 11 ].…”
Section: Notesmentioning
confidence: 99%
“…For instance, several proteomic studies have revealed the presence of urinary extracellular vesicles that contain candidate proteins unique to cancer types that include a broad range of urogenital diseases. 25,26,29,102,110,112,147,157,162 Such tumour-specific vesicles are easily captured from urine using established isolation procedures, which enables repeated tissue sampling.…”
Section: Discussionmentioning
confidence: 99%
“…146 Proteomic analysis of urinary extracellular vesicles has facilitated the identification of an RCC-specific 'fingerprint' , containing proteins such as MMP-9, podocalyxin (PODXL), Dickkopf-related protein 4 (DKK4), carbonic an hydrase IX (CAIX) and ceruloplasmin (Table 4). 147 These preliminary studies suggest that urinary extracellular vesicles could provide a tool for identifying new b iomarkers for RCC, although further studies are needed.…”
Section: Extracellular Vesicles In Rccmentioning
confidence: 92%
“…Therefore, it is necessary to identify and remove proteins that are from the urinary system among proteins found in urine, in order to identify biomarkers for diseases in distal organs [3]. Currently, the most useful disease markers in urine have been largely for urogenital diseases, such as urothelial cancer [4], renal cell carcinoma [5], prostate cancer [6], and bladder cancer [7]. A few recent studies have demonstrated the feasibility in using urinary proteins as disease markers in distal organs, such as ovarian carcinoma [8], lung cancer [9], hepatocellular carcinoma [10], and gastric cancer [11].…”
Section: Introductionmentioning
confidence: 99%